FAKTOR YANG MEMPENGARUHI KEPUASAN COMPLAINT HANDLING TERHADAP LOYALITAS KONSUMEN - Jatmiko, Robby (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
Academics as well as managers have long been interested in the roleof satisfaction with complaint handling (SATCOM) in shapingcustomers’ attitudes and repurchasing decisions. This interest hasgenerated a widespread belief that SATCOM is driven by the perceptionthat the complaint handling process is just. To test how SATCOM ismodulated by distributive, interactional, or procedural justice, weperformed a meta-analysis of 60 independent studies of the antecedentsand consequences of SATCOM. Results indicate that SATCOM isaffected most by distributive justice, then by interactional justice, and onlyweakly by procedural justice. We also find that SATCOM mediates theeffects of justice dimensions on word-of-mouth. However, contrary tocom-mon belief, SATCOM does not mediate the effects of justicedimensions on overall satisfaction and return intent. We draw on ourresults to suggest several avenues for further research.